The Heritage Major within the Bachelor of Arts in International Studies at UTS 1996–2007 - Barbara Leigh (PORTAL: Journal of Multidisciplinary International Studies)
The Heritage Major was introduced in 1994 specifically for those students who had a language facility and ethnic identification with a country that was not offered in the broad suite of sites available to Bachelor of Arts in International Studies (BAIS) students enrolled in country-specific Majors at the University of Technology Sydney (UTS). These are my reflections as the coordinator of the program between 1999 and 2007.